Communicating Archaeology: The magic triangle - Gábor Virágos (Internet Archaeology, 2019)
Needs and interests are two different concepts. Talking about needs, we focus on what would be necessary or ideal to have. This is idealism. Talking about the interests of somebody or a group or a legal entity, we discuss what will happen. This is realism. The two approaches go hand in hand and are yet in opposition to each other.